The Simple Pediatric Activity Ultrasound Score (SPAUSS) for the Accurate Detection of Pediatric Inflammatory Bowel Disease. Issue 1 (July 2019) - Kellar, Amelia; Wilson, Stephanie; Kaplan, Gilaad; DeBruyn, Jennifer; Tanyingoh, Divine; Novak, Kerri L.
ABSTRACT: Objective: The aim of the study was to identify the most significant ultrasound (US) parameters that predict inflammatory activity and develop a simple US activity score. Methods: Patients were identified through retrospective evaluation of an established database of children with inflammatory bowel disease (IBD). Patients with endoscopy and US within 60 days were included (N = 75). US parameters evaluated included: bowel wall thickness (BWT), mesenteric inflammatory fat, lymphadenopathy, and hyperemia. The weighted kappa statistic was calculated to assess agreement between sonographic and endoscopically identified disease location. Using a proportional odds model and ordinal logistic regression, statistically significant ( P < 0.05) parameters were used to generate a score. Variables were weighted to classify individuals into severity classes. Receiver operating characteristic curves were plotted to demonstrate the score's discriminative and predictive capacity. Results: There was substantial agreement between US and endoscopy for all disease locations (weighted kappa = 0.85) and substantial agreement for ileocolonic disease (weighted kappa = 0.96). Two sonographic parameters were identified as contributing significantly to disease activity: BWT and mesenteric inflammatory fat ( P < 0.05). A predictive score was developed incorporating BWT, hyperemia and inflammatory fat, and receiver operating characteristic curve curves demonstrated good predictive capacity to distinguish between the absence of disease (normal) and active disease with an area under the curve of 82.1%. Conclusions: The most important sonographic parameters for predicting disease activity were BWT and mesenteric inflammatory fat. When combined with hyperemia into a simple score, there was accurate detection of inflammatory activity in children with inflammatory bowel disease. This score may facilitate noninvasive, bedside detection of inflammation, and standardize the use of US in children.